Permainan Edukasi untuk Meningkatkan Kemampuan Motorik Halus pada Anak Usia Dini - Lubis, Muhammad Alridho; Sulastri , Dewi; Danuarta, Dino; Sinaga, Indah Erfa; Aliza, Nur (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Fine motor development in early childhood is an important aspect that influences children's learning abilities and social adaptation. Educational games are an effective method for stimulating and improving fine motor skills in children. This research aims to improve children's fine motor skills and cooperation between groups. The colleagues in this activity program are the Simpang Sungai Duren Village Office as the person in charge, and the research subjects involve children aged 5-10 years with the results obtained improving children's fine motor skills and cooperative abilities in groups. This program contributes to the understanding of the role of educational games in fine motor development in young children. The practical implications of this research include the integration of educational games in the development of training programs for teachers in order to optimize the use of educational games in early childhood education environments.